Analysis of Factors Leading to E-commerce Adoption - Agus Dedi Subagja (CV. Media Digital Publikasi Indonesia, 2023)
E-commerce, in particular, is making extensive use of the latest innovations in information technology. The rise of online shopping provides companies with a new channel for expanding their operations. Despite this, many individuals lack an understanding of what drives businesses to embrace e-commerce. The purpose of this research is to illuminate the considerations that companies take into account when deciding to implement e-commerce. This research used a qualitative descriptive approach and a literary analysis to gather information. The findings of this research indicate that there are a variety of organizational elements, including technological, organizational, and environmental, that contribute to the adoption of e-commerce. The study's findings should provide further context for discussions of the elements that influence businesses' decisions to adopt e-commerce.